The Effect of Simulation Puzzle Games on Increasing Mother's Knowledge about Stunting Prevention and Feeding Patterns In Children aged 0-24 Months - Apriani Susmita Sari; Nurrannisa Fitria Aprianti (Babali Publisher, 2023)
Background: Stunting is a condition where a person's height is shorter than the height of other people in general (of the same age). Factors that influence the incidence of stunting are the mother's knowledge about stunting prevention and feeding patterns. Knowledge results from knowing after people have sensed a particular object. The feeding pattern is the mother's way of giving food to children aged 0-24 months. Objectives: This study aims to determine the effect of the simulation games puzzle on increasing mothers' knowledge about stunting prevention and feeding patterns in children aged 0-24 months. Methods: The research design was quasi-experimental with a non-equivalent (pretest and post-test) control group design. Results: There was a significant difference in mother's knowledge about stunting prevention in the simulation game puzzle and booklet group after education (p=0.032), and there was a significant difference in feeding patterns for children aged 0-24 months in the simulation game puzzle and booklet group after education (0.043). Conclusion: Simulation puzzle games and booklets can effectively be used as educational media in increasing mothers' knowledge about stunting prevention and feeding patterns in children aged 0-24 months.